Question: mapping a function to an equation

January 04 2014 taro 90
Maple

0

Hello

I calculated following two expressions, x1,and x2.

x1:=map(f,a+b);

x2:=map(f,y=a+b);

 

The results of these are

f(a) + f(b)

f(y) = f(a + b)

for each. And, I can understand the logic of this.

 

If I want to derive the result of x2 as f(y)=f(a)+f(b), how should I do about x2?

Isn't there other way than to write

map(f, lhs(x2))=map(f,rhs(x2))

?

Please teach me this.

Thank you in advance.

Taro

 

 

Please Wait...